Implementation of the data acquisition system for the Overlap Muon Track Finder in the CMS experiment. (19th January 2017) - Zabołotny, W.M.; Bluj, M.; Buńkowski, K.; Byszuk, A.P.; Dobosz, J.; Doroba, K.; Drabik, P.; Górski, M.; Kalinowski, A.; Kierzkowski, K.Z.; Konecki, M.; Okliński, W.; et al.
Abstract: The Overlap Muon Track Finder (OMTF) is the new system developed during the upgrade of the CMS experiment which includes the upgrade of its Level-1 trigger. It uses the novelty approach to finding muon candidates based on data received from three types of detectors: RPC, DT, and CSC . The upgrade of the trigger system requires also upgrade of the associated Data Acquisition (DAQ) system. The OMTF DAQ transmits the data from the connected detectors that were the basis for the Level-1 trigger decision. To increase its diagnostic potential, it may also transmit the data from a few bunch crossings (BXes) preceding or following the BX, in which the L1 trigger was generated. The paper describes the technical concepts and solutions used in the OMTF DAQ system. The system is still under development. However, it successfully passed the first tests.